Knowledge Level of Dry Skin Care in The Elderly at The Koto Tangah Regional Health Center - Fuji Lestari Kursiussamawati; Irma Primawati; Sriwahyuni Sriwahyuni (Fakultas Kedokteran Universitas Sriwijaya, 2024)
Introduction. The occurrence of dry skin in the elderly requires good and extra skin care. The incidence and severity of dry skin increases with age. Dry skin conditions in the elderly can cause discomfort and can even cause disease, such as atopic dermatitis which is a disease caused by inflammation of the skin. This research aims to determine the level of knowledge of dry skin care in the elderly at the Koto Tangah Health Center in the city of Padang. Methods. This research was a descriptive observational study with a cross-sectional design. The sample in this study was selected by technique consecutive sampling and this research requires a minimum of 100 samples. Results. The knowledge level of dry skin care of the respondents is mostly in the medium category (62%), the age of the majority of respondents was in the age category of 60-70 years (65%), the sex of the majority of respondents was male (53%), most respondents had primary school education (56%), worked as laborer (26%), and live with their families (83%). Conclusion. The level of knowledge of nursing for most of the elderly dry skin is in the medium category.